Keiferia azapaensis sp. nov., the first representative of the New World micromoth genus Keiferia Busck (Lepidoptera, Gelechiidae) associated with a member of Asteraceae - Héctor Vargas (Biodiversity Data Journal)
The New World micromoth genus Keiferia Busck, 1939 (Lepidoptera, Gelechiidae, Gelechiinae, Gnorimoschemini) includes 21 described species, ten of which occur in South America. Like the tomato pinworm, K. lycopersicella (Walsingham, 1897), all the species of Keiferia, whose host plants have been documented, are associated exclusively with members of the family Solanaceae.Keiferia azapaensis sp. nov. is described and illustrated, based on adults reared from leaf miner larvae collected on the shrub Trixis cacalioides (Kunth) D. Don (Asteraceae) in the Atacama Desert, northern Chile. Despite this unusual host plant, a Maximum Likelihood analysis, based on mitochondrial DNA sequences, placed the new species within a well-supported Keiferia clade. The discovery of the trophic association between K. azapaensis sp. nov. and T. cacalioides represents the first record of a member of Asteraceae as a host plant for the micromoth genus Keiferia.